Glycoprotein M6B suppresses the maintenance of glioma stem cell stemness and proliferation via the integrin β1/β-catenin pathway - Chen, Yanwen; Fan, Yu; Run, Xingda; Liu, Maotang; Jiang, Shiwei; Miao, Zengli; Tian, Wei (Frontiers in Molecular Biosciences, 2025)
BackgroundGliomas are highly aggressive intracranial tumors associated with poor prognosis. Glioma stem cells (GSCs) have been shown to play a pivotal role in tumor progression. Previous studies indicate that GPM6B expression correlates with glioma grade and neuronal differentiation. However, the precise mechanisms of GPM6B in glioma remain unknown. In this study, we aim to elucidate the regulatory role of GPM6B in glioma.MethodsThe relationship between the expression of GPM6B and glioma was analyzed using the CGGA and TCGA databases. Western blot analysis was performed to further validate GPM6B expression in clinical samples. The interaction between GPM6B and the Wnt signaling pathway was explored using co-immunoprecipitation, mass spectrometry, quantitative real-time PCR, and Western blot. These findings were further confirmed in cells transduced with different lentiviral constructs. Tumor sphere formation and extreme limiting dilution assays were conducted to assess the stemness of glioma stem cells. Finally, the role of GPM6B in glioma progression was validated in nude mouse models.ResultsThe expression of GPM6B was negatively correlated with glioma grade and prognosis. GPM6B was co-localized with Integrin β1 on the cell membrane. The interaction between GPM6B and Integrin β1 inhibited the expression of β-catenin and its downstream proteins, including p-STAT3, c-Myc, and SOCS3. Moreover, SOCS3 promoted the degradation of GPM6B. Overexpression of GPM6B suppressed tumor sphere formation and reduced the sphere formation efficiency of glioma stem cells. In addition, GPM6B overexpression markedly inhibited the tumorigenic effects of β-catenin and SOCS3. These findings were confirmed in vivo experiments.ConclusionThe expression of GPM6B was negatively correlated with the grade and prognosis of glioma. GPM6B promoted the transformation of glioma stem cells and inhibited growth of glioma by suppressing Integrin β1–mediated regulation of β-catenin, while reducing its own degradation through inhibition of the ubiquitinase SOCS3, thereby stabilizing its function in glioma. Collectively, these results identify GPM6B as a critical regulator of glioma stemness and a potential therapeutic target for glioma, providing new insights into glioma biology and offering a foundation for future translational research.